The two ultraluminous X-ray sources in the galaxy NGC 925. Issue 3 (4th July 2018) - Pintore, F; Zampieri, L; Mereghetti, S; Wolter, A; Rodríguez, G; Israel, G L; Esposito, P; Paiano, S; Trinchieri, G; Ochner, P
ABSTRACT: NGC 925 ULX-1 and ULX-2 are two ultraluminous X-ray sources (ULXs) in the galaxy NGC 925, at a distance of 8.5 Mpc. For the first time, we analysed high quality, simultaneous XMM–Newton and NuSTAR data of both sources. Although at a first glance ULX-1 resembles an intermediate mass black hole candidate (IMBH) because of its high X-ray luminosity [(2–4) × 10 40 erg s −1 ] and its spectral/temporal features, a closer inspection shows that its properties are more similar to those of a typical super-Eddington accreting stellar black hole and we classify it as a 'broadened disc' ULX. Based on the physical interpretation of this spectral state, we suggest that ULX-1 is seen at small inclination angles, possibly through the evacuated cone of a powerful wind originating in the accretion disc. The spectral classification of ULX-2 is less certain, but we disfavour an IMBH accreting at sub-Eddington rates as none of its spectral/temporal properties can be associated with either the soft or the hard state of Galactic accreting black hole binaries.